2013
DOI: 10.1371/journal.pone.0081086
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis of the Reproductive Organs of the Hermaphroditic Gastropod Lymnaea stagnalis Exposed to Different Endocrine Disrupting Chemicals

Abstract: Many studies have reported perturbations of mollusc reproduction following exposure to low concentrations (ng/L range) of endocrine disrupting chemicals (EDCs). However, the mechanisms of action of these molecules on molluscs are still poorly understood. Investigation of the modifications of protein expression in organisms exposed to chemicals using proteomic methods can provide a broader and more comprehensive understanding of adverse impacts of pollution on organisms than conventional biochemical biomarkers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 87 publications
0
19
0
Order By: Relevance
“…It has nevertheless been observed that EDCs can also disrupt invertebrate physiology. For example, Giusti et al (2013) have shown that tributyltin affected the production of yolk ferritin (i.e. Vg equivalent) in Lymnaea stagnalis, and Xuereb et al (2011) observed that nonylphenol (estrogenic compound) impacted the expression of a vitellogeninlike gene in the amphipod Gammarus fossarum.…”
Section: Introductionmentioning
confidence: 99%
“…It has nevertheless been observed that EDCs can also disrupt invertebrate physiology. For example, Giusti et al (2013) have shown that tributyltin affected the production of yolk ferritin (i.e. Vg equivalent) in Lymnaea stagnalis, and Xuereb et al (2011) observed that nonylphenol (estrogenic compound) impacted the expression of a vitellogeninlike gene in the amphipod Gammarus fossarum.…”
Section: Introductionmentioning
confidence: 99%
“…COX1 expression has previously been highlighted as differentially regulated, though subunit specific, in clam exhibiting intersex, mussels exposed to metals, and snail exposed to EDCs (Ciocan et al, 2012;Varotto et al, 2013;Giusti et al, 2013). A study into the mechanistic toxicity of imposex in mud snail, Ilyanassa obsoleta, induced using the antifoulant compound irgarol, similarly reports COX1 up regulation (Finnegan et al, 2009).…”
Section: Discussionmentioning
confidence: 93%
“…There is a growing body of evidence with respect to the presence of glucocorticoids in the environment adversely affecting aquatic biota . Earlier studies have also showed that environmental contaminants (such as pharmaceutical and personal care products, EDCs, pesticides, and heavy metals) induced malformations or other changes in freshwater snail development and survival . Embryonic developmental toxicity in P. acuta was earlier studied in terms of prominent environmental contaminants such as cadmium , ionic liquids , fluoxetine , and nanoparticles .…”
Section: Discussionmentioning
confidence: 99%